Extrasynaptic α6 subunit-containing GABAA receptors modulate excitability in turtle spinal motoneurons. - Carmen Andres; Justo Aguilar; Ricardo González-Ramírez; David Elias-Viñas; Ricardo Felix; Rodolfo Delgado-Lezama (PLoS ONE, 2014)
Motoneurons are furnished with a vast repertoire of ionotropic and metabotropic receptors as well as ion channels responsible for maintaining the resting membrane potential and involved in the regulation of the mechanisms underlying its membrane excitability and firing properties. Among them, the GABAA receptors, which respond to GABA binding by allowing the flow of Cl- ions across the membrane, mediate two distinct forms of inhibition in the mature nervous system, phasic and tonic, upon activation of synaptic or extrasynaptic receptors, respectively. In a previous work we showed that furosemide facilitates the monosynaptic reflex without affecting the dorsal root potential. Our data also revealed a tonic inhibition mediated by GABAA receptors activated in motoneurons by ambient GABA. These data suggested that the high affinity GABAA extrasynaptic receptors may have an important role in motor control, though the molecular nature of these receptors was not determined. By combining electrophysiological, immunofluorescence and molecular biology techniques with pharmacological tools here we show that GABAA receptors containing the α6 subunit are expressed in adult turtle spinal motoneurons and can function as extrasynaptic receptors responsible for tonic inhibition. These results expand our understanding of the role of GABAA receptors in motoneuron tonic inhibition.